The Role of the Iraqi Company for Deposit Insurance in Reducing the Hoarding (International Journal of Financial, Administrative and Economic Sciences, 2025)
The Iraqi Deposit Insurance Corporation was established in 2019 to protect the funds of small depositors in the event of a bank's insolvency or bankruptcy. Another goal of its establishment was to encourage Iraqi citizens to deposit their money in banks instead of hoarding it at home. The first section of the research methodology discussed the importance, objective, and hypothesis of the research, while the second section highlighted the role of deposit insurance companies, specifically the Iraqi Deposit Insurance Corporation, as well as its role in reducing the phenomenon of hoarding money outside the banking system. The third section compared two commercial banks focused on investment, namely the Iraqi Middle East Investment Bank and the Iraqi Investment Bank. Their final account data was analyzed, specifically the volume of deposits for the six years prior to the establishment of the Iraqi Deposit Insurance Corporation in 2019 and four years after its establishment. It was concluded that, to date, the Iraqi Deposit Insurance Corporation has not played a significant or clear role in increasing the volume of bank deposits. The fourth section addressed the most important conclusions and recommendations.
Keywords: Deposit Insurance Companies; Cash-Hoarding; Bank Deposit Volume